Thermal-hydraulic study in a wire-wrapped 19-rod bundle based on an isotropic four-equation model. (1st December 2022) - Su, Xing-Kang; Li, Xian-Wen; Zhang, Lu; Gu, Long; Fan, Da-Jun
Highlights: The model and solver of the isotropic four-equation are described. Critical validation with experience is carried out and discussed. The relevant calculation results of rod bundles are analyzed in detail. Abstract: The thermal–hydraulic performance of rod bundles with wire spacers is significant for studying Lead–Bismuth Eutectic (LBE) cooled fast reactor. The problem is that using the traditional constant turbulent Prandtl number of 0.85 ∼ 0.9, which is generally derived from the Reynolds analogy hypothesis suitable for conventional fluids, will greatly affect the numerical heat transfer accuracy of LBE having low Prandtl number properties. Thus, a great quantity of development work of four-equation models, which may improve the calculation accuracy of turbulent heat transfer in LBE flows, has been made by researchers, while no commercial code is available. The present work addresses an effort to study the thermal–hydraulic phenomenon in an LBE-cooled 19-rod bundle with wire spacers geometry on a self-compiled CFD solver (iso4eqnFoam), which is implemented by a standard finite volume method and C++ program and developed on OpenFOAM. In particular, the simulation aims to perform fully-developed turbulent stresses and turbulent heat fluxes by solving an isotropic four-equation model, which allows simple zero-fixed-value boundary conditions for turbulent variables and considers the difference between viscous and thermal boundary layer of LBE. The simulation results on a bare 19-rod bundle are first compared with heat transfer experimental data and other simulations to validate the effectiveness of the solver. Then, an LBE-cooled 19-rod bundle with wire spacers is presented with thermal–hydraulic simulations. The result shows that iso4eqnFoam can simulate the turbulent heat transfer of LBE under complex geometry. Finally, the distributions of temperature, temperature fluctuation, and turbulent Prandtl number in the channel of the wire-wrapped rod bundle are reported based on the isotropic four-equation model.